2022
DOI: 10.3389/fspor.2022.957086
|View full text |Cite
|
Sign up to set email alerts
|

The Practice Environment—How Coaches May Promote Athlete Learning

Abstract: The coaching environment is the primary teaching and learning medium for the development of athlete skills. Therefore, by understanding how practice environments are designed to facilitate learning, coaches can make decisions around the structure of specific activities and behavior to promote athlete learning and development. This short review examines the coaching environment literature, with a particular focus on the structure and content within a practice session. The review will highlight the specific acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, conceptualizing coaches as mere “resource managers” akin to NPCs challenges this conventional paradigm, suggesting a shift towards a more collaborative and player-centered coaching philosophy ( 48 ). By relinquishing some control and empowering athletes to make their own choices, coaches can encourage athletes to take ownership of their development and decision-making processes ( 49 , 50 ).…”
Section: Npcs In Video Gamesmentioning
confidence: 99%
“…However, conceptualizing coaches as mere “resource managers” akin to NPCs challenges this conventional paradigm, suggesting a shift towards a more collaborative and player-centered coaching philosophy ( 48 ). By relinquishing some control and empowering athletes to make their own choices, coaches can encourage athletes to take ownership of their development and decision-making processes ( 49 , 50 ).…”
Section: Npcs In Video Gamesmentioning
confidence: 99%
“…Programs for developing technical and tactical skills to reach peak athlete performance (Larkin et al, 2022). Sports coaching is now growing rapidly and is becoming professional, such as knowledge and accountability (Kjaer, 2019).…”
Section: Context Evaluationmentioning
confidence: 99%
“…One particular way the quality of training in dance practice may be improved, relates to examining how information is transferred; or in other words, considering dance teachers’ use of instructions and feedback ( Ericsson et al, 1993 ; Williams and Hodges, 2005 ; Neenan, 2009 ; Badami et al, 2012 ; Abbas and North, 2018 ; Otte et al, 2020 ; Larkin et al, 2022 ). In dance, instructions provide the information about the execution of the skills whereas feedback functions as confirmation, motivation, and guidance for the correction of mistakes ( Wulf et al, 1998 ; Enghauser, 2003 ; Gibbons, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…As briefly summarized above, research from across different performance domains, has shown that components of teachers’ instructions and feedback can have differential effects on learning and performing motor tasks ( Williams and Hodges, 2005 ; Neenan, 2009 ; Badami et al, 2012 ; Abbas and North, 2018 ; Otte et al, 2020 ; Larkin et al, 2022 ). However, relatively little is known about teachers’ use of instructions and feedback in dance specifically.…”
Section: Introductionmentioning
confidence: 99%